Questioning the formalist facet of Kant's approach to music - an application to Mussorgsky, a comparison with Hanslick and a response to Samantha Matherne - Sousa, Tiago (Con-Textos Kantianos. International Journal of Philosophy, 2023)
In this article I explore the formalist facet of Kant's theory of music and how this facet can be reconciled with sensory gratification and emotional expression. I argue that 1) Kant does not give us an adequate notion of musical form, 2) the status that Kant gives to sensations in music is not plausible, and 3) the presence of an emotionally expressive component introduces inconsistencies within Kant’s text. Remarks about the status that Kant assigns to sensations in music are illustrated by analyzing a work by Mussorgsky later orchestrated by Ravel. Kant's formalist facet is problematized through a comparison with Eduard Hanslick's musical formalism. I conclude by examining Samantha Matherne's (2014) proposal to reconcile the aforementioned dimensions. I argue that Matherne's "expressive formalism" does not resolve all the inconsistencies and implausibilities it tries to resolve